(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
This paper discussed the increasing danger of population explosion in Nigeria and its implication to available food supply and social infrastructures. The objective of the paper is to show that over population is the reason for high level of illiteracy, wide spread unemployment, poverty and violent crime. The study reveals that with the rate of population increase in Nigeria if nothing is done, time will come when it will result to environmental hazards, malnutrition and other infectious diseases. It observed that while other countries of the world like China and India with increasing rate of population like Nigeria are making serious efforts through Laws and legislation to combat this population increase. The Nigerian leaders are not putting any effort to fight this menace rather what is taking centre stage in Nigeria is this issue of corruption and embezzlement of government funds. The paper was of the opinion that this attitude of our leaders is what has resulted to unemployment armed robbery, kidnapping, underdevelopment and crises of killing and marginalization. It concluded by suggesting a way forward which includes reduction in early marriages which leads to increase in child bearing, corruption and poverty. Finally, it recommended that the government should encourage the people to do away with outdated customs and traditions which make it possible for people lay more emphasis on male children to the extent that unless they have male children, they will not be satisfied.